Themes and theories : selected essays, speeches, and writings in international law / volume 1 - Higgins, Rosalyn (Oxford University Press, 2009)
As President of the International Court of Justice, Rosalyn Higgins is the world's most senior judge. This two-volume set collects together all of her most important writings as a scholar, a member of the UN Human Rights Committee, and as a judge on the International Court of Justice. As President of the International Court of Justice, Rosalyn Higgins is the world's most senior judge. This two-volume set collects together all of her most important writings as a scholar, a member of the UN Human Rights Committee, and as a judge on the International Court of Justice.